2020
DOI: 10.3390/foods9101493
|View full text |Cite
|
Sign up to set email alerts
|

Optimisation of Sequential Microwave-Assisted Extraction of Essential Oil and Pigment from Lemon Peels Waste

Abstract: In this work, a cascade approach to obtain different valuable fractions from lemon peels waste was optimised using microwave-assisted processes. Microwave-assisted hydrodistillation (MAHD) with a Clevenger apparatus was firstly used to obtain the lemon essential oil (LEO). The remaining residue was then submitted to microwave-assisted extraction (MAE) to extract the lemon pigment (LP). A Box–Behnken design was used to evaluate the influence of ethanol concentration, temperature and time in LP extraction in ter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 55 publications
(15 citation statements)
references
References 50 publications
0
15
0
Order By: Relevance
“…The quadratic regression equation generated according to extraction time, temperature, and ethanol concentration had an R 2 of 0.9237, implying that the sample variation of 92.37% was attributed to the independent variables, and only 7.63% of the total variations could not be explained by the model ( Table 3 ). This indicates a good degree of correlation between the predicted and experimental values of the CIA and recognizes its suitability in predicting the experimental model [ 39 ]. ANOVA demonstrated statistical significance ( p = 0.0037) below a significance level of 1% and confirmed that the extraction temperature ( p = 0.0030) and ethanol concentration ( p = 0.0006) among the linear terms were independent variables that significantly affected CIA ( Table 4 ).…”
Section: Resultsmentioning
confidence: 95%
“…The quadratic regression equation generated according to extraction time, temperature, and ethanol concentration had an R 2 of 0.9237, implying that the sample variation of 92.37% was attributed to the independent variables, and only 7.63% of the total variations could not be explained by the model ( Table 3 ). This indicates a good degree of correlation between the predicted and experimental values of the CIA and recognizes its suitability in predicting the experimental model [ 39 ]. ANOVA demonstrated statistical significance ( p = 0.0037) below a significance level of 1% and confirmed that the extraction temperature ( p = 0.0030) and ethanol concentration ( p = 0.0006) among the linear terms were independent variables that significantly affected CIA ( Table 4 ).…”
Section: Resultsmentioning
confidence: 95%
“…The obtained results showed coefficients of determination for extraction yield, TPC and ABTS of 0.7959, 0.8061, and 0.8446, respectively, indicating the model's accuracy and a reasonable degree of correlation between experimental and predicted values (62). In addition, the lack of fit was not significant, obtaining high p-values (p > 0.05) (0.2186, 0.1868, and 0.1584 for yield, TPC, and ABTS, respectively), verifying the good fit of the proposed models to predict polyphenols extraction from DP under the studied experimental region (65). According to the obtained F values, the most and least influencing factors on the studied responses were ethanol concentration and time, respectively.…”
Section: Microwave-assisted Extraction Optimization From Dry Powdermentioning
confidence: 60%
“…Despite the fact that natural additives have many advantages and can be successfully used as biocides, it must also be remembered that natural extracts may be less active compared with chemical equivalents, and have a shorter period of action. However, the presented research shows that this topic is very interesting because it concerns the use of organic substances in polymer materials [72][73][74][75][76][77][78][79][80][81][82]. The antimicrobial properties of the polyurethane were rated toward E.coli and S. aureus and others.…”
Section: Discussionmentioning
confidence: 99%